A rare case of acute myeloid leukemia with der(1)t(1;19)(p13;p13.1). (2019) - McAlice, Meghan; Gohar, Munaza; Alshaban, Ahmed; Orazi, Attilio; Tonk, Vijay; Chavali, Santosh; Tonk, Sahil; Gaur, Sumit
Abstract: We present a case of acute myeloid leukemia with der(1)t(1;19)(p13;p13.1) translocation and RUNX1 mutation. A literature review summarizing the clinical, pathological, and molecular features of the published cases is also presented.